2017
DOI: 10.3390/nu9060615
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Probiotics in Health and HIV Infection

Abstract: Microbiota play a key role in various body functions, as well as in physiological, metabolic, and immunological processes, through different mechanisms such as the regulation of the development and/or functions of different types of immune cells in the intestines. Evidence indicates that alteration in the gut microbiota can influence infectious and non-infectious diseases. Bacteria that reside on the mucosal surface or within the mucus layer interact with the host immune system, thus, a healthy gut microbiota … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 128 publications
(161 reference statements)
2
42
0
Order By: Relevance
“…Moreover, in HIV positive subjects as well as in negative individuals, phenylalanine and tyrosine represent precursors involved in the synthesis of catecholamines, such as dopamine; Phe/Tyr is usually considered a marker of the activity of tetrahydrobiopterin, the enzyme that catalyzes the first step of the pathway of catecholamines synthesis (the transformation of phenylalanine into tyrosine), therefore an elevated Phe/Tyr has been associated with a reduced level of dopamine [14] and subsequently with imbalanced cognitive abilities. Compared to total amino acids, the impairment in the enzymatic conversion of Phe is strongly related to clinical symptoms like depressive mood [26][27][28] and the worsening of life quality [29][30][31] , especially in HIV-1 infected patients, due to the association between the Phe metabolism and HIV-1 pathology [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in HIV positive subjects as well as in negative individuals, phenylalanine and tyrosine represent precursors involved in the synthesis of catecholamines, such as dopamine; Phe/Tyr is usually considered a marker of the activity of tetrahydrobiopterin, the enzyme that catalyzes the first step of the pathway of catecholamines synthesis (the transformation of phenylalanine into tyrosine), therefore an elevated Phe/Tyr has been associated with a reduced level of dopamine [14] and subsequently with imbalanced cognitive abilities. Compared to total amino acids, the impairment in the enzymatic conversion of Phe is strongly related to clinical symptoms like depressive mood [26][27][28] and the worsening of life quality [29][30][31] , especially in HIV-1 infected patients, due to the association between the Phe metabolism and HIV-1 pathology [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, more data are necessary before firm conclusions can be drawn. Supplementation of antiretroviral (ARV) therapy with oral probiotics showed the ability to modulate gut microbial species, restoring gut mucosal immunity and thus potentially decreasing microbial translocation and immune activation [16][17][18]. Furthermore, probiotics showed the ability to improve neurocognitive function and reduce immune activation in this population [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of external emulsions is to improve digestion by increasing the formation of emulsified droplets that reduce surface tension and stimulate the formation of lipid particles and increase the concentration of monounsaturated fats in the intestines and thus facilitate the transfer of digested food through the walls of the intestines and facilitate the absorption process and power processing (20,21) and this will improved fat and protein digestion (22). Probiotic in poultry have several actions include maintaining normal intestinal microflora by competitive exclusion antagonism, competing for mucosal attachment, lowering the pH through acid fermentation, stimulating the immune system associated with the gut, producing bacteriocins and increasing production of short-chain fatty acids Chiara et al (23). The most characteristics of the probiotic are to compete with pathogenic bacteria on the adhesion site of the target organ, these site are usually in the gastrointestinal tract and the female reproductive canal and its adhesion ability is due to adhesion factors on the surface of the probiotic and existing receptors in host cells and especially epithelial cells in the intestine (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since imbalances of gut bacterial species (dysbiosis) and increased microbial translocation have been observed in HIV-positive patients (Xu et al 2013;Salas and Chang 2014;Hunt et al 2014), any intervention which is able to protect the gut barrier should be explored. Previously, we have shown that the supplementation with a high concentration multistrain probiotic formulation to cART patients was associated with the recovery of the gut epithelial barrier integrity, a reduction in both intraepithelial lymphocyte density and enterocyte apoptosis, and an improvement in mitochondrial morphology (d' Ettorre et al 2014Ettorre et al , 2017Carter et al 2016;D'Angelo et al 2017;Pinacchio et al 2018). We also observed that different neurocognitive test scores improved significantly after probiotic supplementation (Ceccarelli et al 2017a, b;Akbari et al 2016).…”
Section: Introductionmentioning
confidence: 99%